Upaya Meningkatkan Pemahaman Konsep Peran Indonesia Dalam ASEAN Dengan Metode Pembelajaran Multikultural di Kelas VI SDN Sananwetan 2 Kecamatan Sananwetan Kota Blitar - Wiwik Yuliani (Civiliza Publishing, 2021)
Abstract. With the existence of social studies subjects in elementary schools, students are expected to have knowledge and insight about the basic concepts of social science and humanities, have sensitivity and awareness of social problems in their environment, and have the skills to study and solve these social problems. However, learning is currently experiencing obstacles because of online learning. Student learning outcomes are decreasing, due to the lack of appropriate teaching methods in online learning. Under these conditions, research is needed in class VI SDN Sananwetan 2, Sananwetan District, Blitar City. The type of research used is Classroom Action Research (CAR). Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The learning method used is the Multicultural learning method, which is an attitude in looking at the uniqueness of humans without distinguishing race, culture, gender, physical condition or one's economic status. Within the scope of education, a learning that includes multicularism is needed so that students can recognize and respect the diversity of other social groups.